Inflammatory Mechanisms in the Management and Treatment of Retinal Detachment - Pablo Redruello-Guerrero; María Gómez-Tomás; Tomás Rechi-Sierra; Laura Molinero-Sicilia; Nadia Galindo-Cabello; Ricardo Usategui-Martín; Salvador Pastor-Idoate (Metabolites)
Retinal detachment (RD) is a serious clinical condition that significantly impacts patients’ quality of life. Its management involves considering several clinical factors that may affect the therapeutic approach. Inflammatory complications can affect visual recovery, long-term outcomes, and prognosis. Understanding the underlying inflammatory mechanisms is key to improving personalized medicine and optimizing therapeutic approaches to management. This review comprehensively searched scientific databases (Medline, Web of Science, and Scopus), considering clinical and experimental studies published between 1999 and 2025. Specific MeSH terms and predefined inclusion and exclusion criteria were used to select the most relevant papers. A total of 140 studies were analyzed. The findings were analyzed qualitatively and illustrated with images from clinical practice. Several studies have demonstrated the critical role of cytokines in retinal inflammation, highlighting their importance in regulating the immune response following RD. In addition, oxidative stress, apoptotic mechanisms, and glia activation, particularly Müller cells and microglia, have been identified as crucial elements in the progression of retinal damage. In this sense, inflammation poses significant clinical challenges that require more effective therapeutic strategies. In conclusion, this review differs from previous literature by emphasizing the translational implications of inflammatory mechanisms in RD and by comparing experimental and clinical data. The management of RD should consider not only surgical aspects, but also modulation of the inflammatory response to improve visual outcomes and prevent long-term complications.